PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH (STUDI KASUS GURU-GURU SMP NEGERI DI KECAMATAN PATI KABUPATEN PATI) - Matni, 1252020022 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to identify and examineÂ the influence of motivation and work discipline on the teacherâs performance by moderationhead master leadership that takes an objectof primary school teachers in Pati subdistrict Pati Regency. Sampling was done by purposive sampling technique. From the result of purposive sampling, the sample was used in this study, total 179 people. Testing data technique which is used in this study include validity test by factor analysis, reliability test by Cronbach alpha formula, multiple regression analysis, and significanceÂ tests, the coeffisien of determination to prove the hypothesis and moderation regressionanalysis. The result showed that the variables of motivation haspositive and significanteffect of teacherâs performance. Variables of discipline not significanton teacherâs performance.Principalâs leadership haspositiveand significanteffect of teacherâs performance of primary schoolâs teachers in Pati subdistrict Pati regency. Principalâs leadership can increase work motivation on teacherâs performance, but principalâs leadership can decrease work discipline on teacherâs performance. Key word : motivation, discipline, principalâs leadership, performance